Diagnostic value of lung function tests in long COVID: analysis of positive bronchial provocation test outcomes - Liu, Wei; Feng, Qixuan; Yuan, Xuefeng; Lu, Chang; Wang, Shuang; Yuan, Yadong (Frontiers in Medicine, 2025)
BackgroundLong COVID patients are prone to bronchial hyperresponsiveness and respiratory symptoms like coughing and breathing difficulties, often with positive bronchial provocation test (BPT) results.ObjectiveThis study aims to evaluate the diagnostic value of various lung function tests in patients with long-term COVID-19, explicitly focusing on positive BPT outcomes.MethodsOur study analyzed the BPT outcomes and various pulmonary function parameters of all 9,406 COVID-19 patients who met the inclusion criteria and visited our hospital between February 24, 2022, and April 28, 2024. Key indicators included forced vital capacity (FVC), forced expiratory volume in one second (FEV1), peak expiratory flow (PEF), and single-breath diffusing capacity for carbon monoxide (DLCOc SB). A logistic regression model was employed to identify factors influencing positive BPT results, while the receiver operating characteristic (ROC) curve was used to assess the diagnostic efficacy of these indicators.ResultsA total of 4211 valid samples were analyzed, with 3388 patients (80.46%) testing positive for BPT. Significant differences were observed between positive and negative groups regarding age, gender, smoking status (all P < 0.05), and specific lung function indicators, including FVC, FEV1/FVC ratio, maximum of vital capacity (VC max), and DLCOc SB (all P < 0.001). Logistic regression identified age, MEF50, and DLCOc SB as independent factors influencing positive BPT results. The area under the ROC curve for all assessed factors was <0.700, indicating limited diagnostic value.ConclusionAge, the small airway function indicator MEF50, and the pulmonary diffusion function indicator DLCOc SB are independent influencing factors for BPT positivity in long-term COVID patients. However, baseline data and lung function indicators have limited utility for diagnosing positive BPT in this population, highlighting the complex nature of post-COVID respiratory symptoms.